Використання смартфона з веб-застосунком як бездротового контролера в багатокористувацьких іграх на основі технології постійного підключення WebSocket - Двугрошев, А. О. (ХНУРЕ, 2024)
The current work explores the use of a mobile web application as a game controller using WebSocket technology. The development of such a tool involves the transfer of the main game logic to the server, while the environment display client computes the entire visualization of the game, significantly reducing the load on the overall system. Using mobile game controller systems, in turn-based games the game mechanic ensures efficient execution of in-game events with minimal feedback from the system. The work used the Node.js runtime environment, the React library, and the TypeScript and JavaScript programming languages.
Keywords: сматрфон; веб-застосунок; бездротовий контролер; багатокористувацька гра; WebSocket; game